Customer attitudes towards organic products and their impact on satisfaction - an empirical study. (2nd June 2023) - Sankar, C.; Aruna, J.
Consumer behaviour in buying the products rests with their psychological, personality, and other external motivational factors. Analysing the buying process towards the new arrival in the market is complicated as the pattern cannot be judged by anybody. Customers do not change their options unless clearly understanding the benefits of those new ones. It has been applied to the organic products also now emerging in the market. This study has attempted to examine the customer mind-set in buying the organic products along with its effect on their satisfaction with 586 customers selected through simple random sampling from various states of India. The researcher has applied various statistical tools, and the result revealed that all the constructs have a positive and significant effect on the customer attitude except the price of the organic products. Also, there exists a negative impact of customer attitude on satisfaction, but the effective marketing strategies and the promotional aspects that changed the effect into a positive one. Marketers should analyse the reason for the low traffic of sales despite having more awareness and health consciousness among the customers and implement innovative strategies to overcome the barrier.